Soil-surface CO2 flux during the first 2 years after stump harvesting and site preparation in 14 Swedish forests. Issue 3 (3rd April 2017) - Strömgren, Monika; Mjöfors, Kristina; Olsson, Bengt A.
ABSTRACT: Stumps are a source of renewable energy (bioenergy) that can mitigate climate change. We aimed to determine whether conclusions from recent studies could be generalized for other sites by monitoring the in situ soil respiration (Rs ) by a portable soil-respiration system of 14 clear-cut experimental sites during the first 2 years after stump extraction and site preparation. The sites were established all over Sweden in 2013 and 2014 and were subjected to no disturbance (Control), patch scarification (PatchS), disc trenching (DiscT), and stump harvesting (StumpH). During year 1, Rs from sites treated with PatchS and StumpH were 11% and 13% lower than Rs from Control sites. DiscT-treated sites were apt to produce lower Rs than the Control (−9%, p = .09). In the second year, there were no significant differences in Rs between treatments, as no soil disturbance type occurring after stump harvest and site preparation had higher Rs than untreated, intact soil. Our results suggest that soil disturbances resulting from stump harvest and site preparation do not generally increase Rs and thus, from this perspective, provide support for the use of stumps for bioenergy.